2007
DOI: 10.1186/1472-6750-7-36
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of miRNA expression patterns using total RNA extracted from matched samples of formalin-fixed paraffin-embedded (FFPE) cells and snap frozen cells

Abstract: Background: Archival formalin-fixed paraffin-embedded (FFPE) tissues have limited utility in applications involving analysis of gene expression due to mRNA degradation and modification during fixation and processing. This study analyzed 160 miRNAs in paired snap frozen and FFPE cells to investigate if miRNAs may be successfully detected in archival specimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
240
0
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(255 citation statements)
references
References 17 publications
4
240
0
6
Order By: Relevance
“…[27][28][29] Our micro-RNA-based qRT-PCR test has been developed and validated using retrospective FFPE samples with established primary origins. Our technology is highly sensitive and is applicable also to fresh frozen and small samples such as are obtained with fine needle aspirates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29] Our micro-RNA-based qRT-PCR test has been developed and validated using retrospective FFPE samples with established primary origins. Our technology is highly sensitive and is applicable also to fresh frozen and small samples such as are obtained with fine needle aspirates.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26] MicroRNAs are also stable in tissue, stored frozen or as formalinfixed, paraffin-embedded (FFPE) samples, and in serum. [27][28][29] In an earlier work, we showed that a biologically motivated classifier based on expression of a relatively small number of tissue-specific microRNAs allows tumor tissues of origin to be accurately identified. 26 A small number of markers can be measured by quantitative reverse transcriptase polymerase chain reaction (qRT-PCR), which is a well-established platform for diagnostic assays.…”
mentioning
confidence: 99%
“…[145][146][147] It is noteworthy that standard formalin-fixation and paraffin-embedding of tissues seems to preserve microRNAs in a reasonably intact and extractable state. 146,148,149 Once these tools are clinically validated more extensively, they should enable microRNA measurements to become a part of the pathologist's diagnostic armamentarium.…”
Section: Practical Aspectsmentioning
confidence: 99%
“…20,21,23,24 MicroRNAs are stable in formalin-fixed paraffin-embedded samples. 28,29 Tumor cells in pancreatic ductal adenocarcinomas are often located in small groups surrounded by an abundant stromal tissue 30 and information related to microRNAs from the stromal tissue may be lost if micro-dissection is applied.…”
mentioning
confidence: 99%